Why have we not yet developed a simple blood test for TBI?. (May 2015) - Plog, Benjamin A; Nedergaard, Maiken
Abstract : In recent years, traumatic brain injury (TBI) has emerged as a rapidly growing public health challenge. Annually, approximately 1.7 million people will sustain a TBI in the USA and WHO has named TBI the leading cause of death and disability in young adults worldwide, predicting it will become the third leading cause of death in the general population by 2020. The medical community currently relies on clinical examination and various neuroimaging modalities for the diagnosis of TBI; however, these methodologies are often confounded by altered patient mental status and are particularly poor at identifying mild-to-moderate injury. Despite decades of basic and clinical research, and the identification of hundreds of biochemical markers, presently there is no blood test to objectively assess TBI severity. Recent work suggests treatment-induced variance in the brain's glymphatic clearance may be responsible for the breakdown between biomarker discovery and clinical translation.